HEDGE-ALGEBRAS-BASED FUZZY CONTROLLER: APPLICATION TO ACTIVE CONTROL OF A FIFTEEN-STORY BUILDING AGAINST EARTHQUAKE - Ho, Nguyen Cat; Lan, Vu Nhu; Trung, Tran Duc; Le, Bui Hai (Vietnam Journal of Science and Technology, 2012)
Active control problem of seism-excited civil structures has attracted considerable attention in recent years. In this paper, conventional, hedge-algebras-based and optimal hedge-algebras-based fuzzy controllers, respectively denoted by FC, HAFC and OHAFC, are designed to suppress vibrations of a structure with active tuned mass damper (ATMD) against earthquake. The interested structure is a high-rise building modeled as a fifteen-degree-of-freedom structure system with two type of actuators installed on the first storey and fifteenth storey which has ATMD. The structural system is simulated against the ground accelerations, acting on the base, of the El Centro earthquake in USA on May 18th. The control effects of FC, HAFC and OHAFC are compared via the time history of the storey displacements of the structure.